Protective Effects of Tinospora cordifolia on Cyclophosphamide-induced Nephrotoxicity in Wistar Rats - Yadav, Ram Naresh; Ganeshpurkar, Aditya; Dubey, Nazneen (Free Radicals and Antioxidants)
Background: Nephrotoxicity induced by drugs is a common cause of renal failure, particularly with agents like cyclophosphamide used in cancer treatment. Natural antioxidants found in plants offer diverse therapeutic benefits. Tinospora cordifolia, a medicinal plant known for its hepatoprotective, diuretic, carminative, digestive, and anti-helminthic properties, was investigated for its potential to counter cyclophosphamide-induced kidney damage in rats. Materials and Methods: Extracts were prepared from dried Tinospora powder, rich in flavonoids, polyphenolics, and alkaloids. Rats were divided into control and treatment groups, with varying doses of the Tinospora extract alongside cyclophosphamide. The blood sample was evaluated for creatinine, urea and BUN. Results: Treatment with the extract, particularly at 400 mg/kg, significantly reduced creatinine levels, as well as serum urea and blood urea nitrogen (p<0.01). These results highlight Tinospora cordifolia's nephroprotective potential, attributed to its flavonoid and polyphenol content. Conclusion: This study underscores the promise of plant-derived compounds in mitigating drug-induced kidney damage, suggesting Tinospora cordifolia as a potential adjunct therapy to preserve renal function during chemotherapy. Further research is needed to elucidate mechanisms and validate these findings for clinical application.
Keywords: Tinospora cordifolia; Nephroprotection; Cyclophosphamide; Renal function; Wistar rats